Patient preferences for maintenance therapy in Crohn's disease: A discrete-choice experiment. - Glen S Hazlewood; Gyanendra Pokharel; Robert Deardon; Deborah A Marshall; Claire Bombardier; George Tomlinson; Christopher Ma; Cynthia H Seow; Remo Panaccione; Gilaad G Kaplan (PLoS ONE)
Objective To quantify patient preferences for maintenance therapy of Crohn's disease and understand the impact on treatment selection. Methods We conducted a discrete-choice experiment in patients with Crohn's disease (n = 155) to measure the importance of attributes relevant to choosing between different medical therapies for maintenance of Crohn's disease. The attributes included efficacy and withdrawals due to adverse events, as well as dosing and other rare risks of treatment. From the discrete-choice experiment we estimated the part-worth (importance) of each attribute level, and explored preference heterogeneity through latent class analysis. We then used the part-worths to apply weights across each outcome from a prior network meta-analysis to estimate patients' preferred treatment in pairwise comparisons and for the overall group of treatments. Results The discrete-choice experiment revealed that maintaining remission was the most important attribute. Patients would accept a rare risk of infection or cancer for a 14% absolute increased chance of remission. Latent class analysis demonstrated that 45% of the cohort was risk averse, either to adverse events or requiring a course of prednisone. When these preferences were used in modelling studies to compare pairs of treatments, there was a ≥ 78% probability that all biologic treatments were preferred to azathioprine and methotrexate, based on the balance of benefits and harms. When comparing all treatments, adalimumab was preferred by 53% of patients, who were motivated by efficacy, and vedolizumab was preferred by 30% who were driven by the preference to avoid risks. However, amongst biologic treatment options, there was considerable uncertainty regarding the preferred treatment at the individual patient level. Conclusion Patients with Crohn's disease from our population were, on average, focused on the benefits of treatment, supporting intensive treatment approaches aimed at maintaining remission. Important preference heterogeneity was identified, however, highlighting the importance of shared decision making when selecting treatments.